Vegetation’s Structure and Compotition to Support the Javan Gibbon (Hylobates Moloch) Habitat Sustainability in Gunung Halimun National Park - Suryanti Rostian, T. (International Journal of Engineering and Technology, 2019)
There are a few disturbances which could affect landscapeâ€™s structure and function, for instance increased population and development growth. These are also consequences of development of facilities to support human activity. Mount Halimun National Park territory supports the biggest population of Javan Gibbon (Hylobates moloch) in Java. There are few factors which affect forests destruction in Gunung Halimun namely transporation facilities, tea plantation enclave, and gold mining. The present study is a part of the landscape analysis for conservation and management of Javan Gibbon in Mount Halimun National Park. The study was conducted at Mount Kendeng which is the Javan Gibbon habitat, at the Mount Halimun, West Java. Elevation of the park area ranging from 570 â€“ 1929 m asl. The wide range of altitudes caused diverse ranges of habitat types also floristic composition. This researxh aims to analyze vegetationâ€™s structure and composition of Javan Gibbon habitat. To spupport Javan Givon habitat sustainably, plant selection is a very important step in the landscape design sequence. We recorded 64 species of trees with DBH > 10 cm in 25 families, with density of 401 trees/hectare and total basal areas of 35,30 m2. Species richness is low which is typical of mountain forests on West Java. Â Â Â Â